Correlation Between Blood Glucose Level and Cerebral Small Vessel Disease Markers in Neurologically Asymptomatic, Nondiabetic Individuals - Xinxin Ma; Fang Liu; Lei Qiu; Juan Chen; Wei Du; Jing He; Aizhen Sheng; Yinhong Liu (Aging Medicine)
ABSTRACT Objectives Cerebral small vascular disease (CSVD) is not rare in neurologically asymptomatic individuals. Glucose control and insulin resistance (IR) may be its risk factors. We aimed to explore the relationship between CSVD markers, glucose control, and IR in neurologically asymptomatic, nondiabetic individuals. Methods A total of 412 participants from the annual physical examinations population in our hospital who underwent brain magnetic resonance imaging from May 2019 to June 2021 were enrolled. We collected clinical data and blood test indices and calculated the triglyceride‐glucose (TyG) index. CSVD markers were assessed, including lacunes, white matter hyperintensities (WMH), enlarged perivascular spaces (EPVS), cerebral microbleeds (CMBs), and the total CSVD score. Correlations between CSVD markers, clinical variables, and blood test parameters were analyzed. Results The median age of our group was 70.32 ± 10.27 years (45–103 years). The prevalence of asymptomatic CSVD was 43.7%. Lacunes were present in 8.3%, periventricular WMH (PVWMH) in 65.3%, deep WMH (DWMH) in 64.1%, EPVS in 87.4%, and CMBs in 31.3% of individuals. Glycated hemoglobin A1c (HbA1c) varied between PVWMH subgroups (p = 0.043). Fasting blood glucose (FBG) was higher in individuals with deep CMBs than in those without deep CMBs (p = 0.012). FBG was an independent risk factor for deep CMBs after controlling for multiple variables. However, the TyG index was not associated with CSVD markers. Conclusions The prevalence of neurologically asymptomatic CSVD is common in the nondiabetic population. It may be beneficial for middle‐aged and elderly people to pay attention to their blood glucose levels.